Development of a Clinical Pathway Model in Increasing Income from BPJS Claims - Andreuw Sunarjo; Erliany Syaodih; Rian Andriani (Universitas Islam Lamongan, 2024)
Application Clinical Pathway in hospitals has been recognized as an effective strategy for improving the quality and efficiency of health services. This study aims to evaluate the effectiveness of Clinical Pathway implementation at Dustira Hospital TNI AD Cimahi, especially in the context of BPJS Health claims and the factors that influence its success. This research uses qualitative methods. The sampling technique uses technique scluster random sampling where the selection of the TNI AD Dustira Hospital was chosen randomly. This data was collected by means of questionnaire surveys, interviews and document analysis. The results of the research show that the implementation of Clinical Pathway is effective in increasing BPJS claim income, which is proven by the fact that in 2022 there was an increase in income in the following year in 2023.